2020
DOI: 10.5114/pq.2020.95772
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of hydrotherapy in patients with chronic low back pain

Abstract: Introduction. Low back pain is the most common musculoskeletal disorder. Hydrotherapy may assist a variety of pathological conditions, including low back pain. The purpose of the study is to examine the effectiveness of hydrotherapy in chronic low back pain. Methods. A comprehensive search of PubMed, MEdLiNE, Elsevier, and Google Scholar was conducted for randomized controlled trials published in the period of 2009-2019 that investigated therapeutic aquatic exercise for low back pain. Particularly, the examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Their findings demonstrated that aquatic exercise could significantly decrease patients' pain intensity and improve their functional level. Similarly, Christakou and Boulnta (Christakou & Boulnta, 2020) revealed in their review a relief of pain and disability and an improvement in quality of life and psychological state following hydrotherapy. On the other hand, Waller et al (Waller et al, 2009) published a systematic review included 7 trials that the methodological quality of all included studies was considered low.…”
Section: Discussionmentioning
confidence: 89%
“…Their findings demonstrated that aquatic exercise could significantly decrease patients' pain intensity and improve their functional level. Similarly, Christakou and Boulnta (Christakou & Boulnta, 2020) revealed in their review a relief of pain and disability and an improvement in quality of life and psychological state following hydrotherapy. On the other hand, Waller et al (Waller et al, 2009) published a systematic review included 7 trials that the methodological quality of all included studies was considered low.…”
Section: Discussionmentioning
confidence: 89%
“…(2022) proved that the superior effects of light aquatic aerobics on mood and anxiety over other modalities. Another review by Christakou and Boulnta (2020) demonstrated that hydrotherapy improved pain, disability, life quality, and psychological status.…”
Section: Discussionmentioning
confidence: 99%
“…While the positive roles of physiotherapy modalities [27,28] and yoga [29][30][31] in improving chronic LBP have been established, this study is the first to investigate the feasibility (i.e., adherence and safety) and the potential effect size of the Sun Salutation in improving pain, functional disability, and QoL among patients with subacute LBP. While a higher intensity exercise is more appropriate for chronic conditions [32], we utilized Sun Salutation because of its low intensity, which may best suit subacute conditions.…”
Section: Discussionmentioning
confidence: 99%